Tenofovir pharmacokinetic after sleeve-gastrectomy in four severely obese patients living with HIV. Issue 1 (January 2017) - Muzard, Ludivine; Alvarez, Jean-Claude; Gbedo, Christophe; Czernichow, Sébastien; Carette, Claire
Summary: There are many unsolved questions about safety of bariatric surgery in the context of severely obese patients living with human immunodeficiency virus (HIV) and notably on antiretroviral therapy (ART) absorption. Here, we provide the first case series of tenofovir disoproxil fumarate (TDF) pharmacokinetic in four HIV-infected patients before and after sleeve-gastrectomy. Our case-series showed a transient and reversible decrease of TDF bioavailability one month after sleeve-gastrectomy without any consequences on CD4 cells and HIV viral load. More studies are needed since the impact of bariatric surgery on drug absorptions in the field of infectious diseases remains poorly investigated.